Analisis Faktor-faktor yang Mempengaruhi Perusahaan di Indonesia Melakukan Auditor Switching (Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2011-2014) - Biantoro, Fredy; , Fauzan, S.E,. M.Si, Akt (2015)
This research aim to know the factors that influence companies in Indonesia to do such auditor switching. Variables that used in this research are management changes, audit opinion, financial distress, change percentage of Return on Assets, public accountant firm's size, client size, and auditor switching. This research uses financial statements data of manufacturing company listed in Bursa Efek Indonesia (BEI) from year 2011-2014. Based on method purposive sampling, research sample total is 140 companies. Hypothesis in this research are tested by logistic regression. Result of this research indicates that variables having which significantly affect the auditor switching are change percentage of Return on Assets and public accountant firm's size. On the other hand, other variables in this research like management changes, audit opinion, financial distress, and client size do not have significant effect on company decision to do auditor switching.